Perdas por evaporação e arraste em sistemas de irrigação por aspersão fixa - Galote, Jean Karlos Barros (2016)
The search for information on evaporation losses and wind drift (PEAV) in fixed sprinkler irrigation system allowed the use of bibliometrics for the dissemination of existing information on research related to Brazilian educational institutions, referring to PEAV sprinkler small and medium businesses. Surveys were conducted in journals indexed in the ISI, Scorpos, Sciello, Google Scholar, using as sources of access "PERIODIC CAPES" and Google Scholar. As a research method was used keywords sprinkler, wind drift losses, evaporation, modeling, spray, evaporation losses, drag the wind and drift, as the main focus of the study, which may be contained in the titles and summaries or specified. The results were processed in a multidimensional database that allows, by means of statistical analysis, generating historical indicators of the subject. Being identified 7 articles published from 1999 to 2013, involving 8 educational institutions and Brazilian research and 28 authors. With water resources becoming increasingly scarce, due to climatic adversities of the past decade the efficient use of water through irrigation becomes essential to modern agriculture, given the constant climate changes, switching the water regimes, and increasing need of conscious and sustainable use of water. Agriculture is responsible xiv for much of its use and waste and even in well-managed irrigation systems, losses are inherent depending on local weather conditions. Knowledge of sprinkler operating characteristics and atmospheric conditions (wind, relative humidity, air temperature, and the vapor pressure deficit) in the area for irrigation allows the suitability of a more efficient system. The losses occur due to evaporation of sprayed droplet, and the wind drift. Based on the above objective of this work performance analysis, quantifying the loss of water by evaporation and wind drift the sprinklers: Zm "8503, Plasnova© MC-20, Asperjato© Junior NY12, operating on the service pressures 155, 207, 258 and 310 kPa, irrigation interval of 60 minute, at different working hours (04h00min, 12h00min, 21h00min) covering the dry and wet periods of the year and had different weather conditions. The observed values were compared with the values estimated by empirical methods proposed by Yazar (1984), Trimmer (1987), Tarjuelo et al. (2000), Playán et al. (2005) and Beskow et al. (2011). For the field tests verified losses from 0.0 to 64.7%. The losses vary with an average of 18.3%. For the time of 4h00min losses ranged from 0.0 to 25.1% for the time from 12h00min ranged from 9.7 to 64.7% and the time of 21h00min ranged from 0.0 to 17.7% . The empirical models used did not obtain good fits, with confidence indexes and performance (c) ranging from "very poor" (c < 0.40) the "average" (0.61 < c <0.65). The model proposed in this work to the sprinkler MC20 presented (c) 0.89, for the sprinkler NY12 (c) was 0.96 for the sprinkler ZM8503 (c) was 0.92, being classified as "great" (c > 0.85).